Incorporating mutation probability into priority-aware protection in optical networks - Fawaz, Wissam (2009)
A persisting major challenge for optical network operators is to meet the various availability requirements of the different subscribed services through the deployment of effective protection strategies. Priority-aware shared protection is a promising scheme that has been proposed in the open literature as a potential approach to tackling this challenge. However, the priority-aware protection strategy is rigid in the sense that it privileges the high priority connections regardless of the low priority ones. Hence, this letter proposes to improve priority-aware protection by introducing the mutation probability parameter. This parameter expresses the likelihood that a high-priority connection be relegated temporarily to a lower priority level during recovery. In this way, the mutation-based protection strategy offers optical operators the possibility to increase the availability of their low-priority clients without violating the availability requirements of their high-priority ones. Performance of this novel protection strategy is analyzed in this letter by precisely calculating the connection availabilities resulting from its deployment.